Senegal National Framework for Climate Services (NFCS): Status & achievements - Ouedraogo, Issa (2025)
This document presents the status and achievements of Senegal’s National Framework for Climate Services (NFCS), established in alignment with the Global Framework for Climate Services (GFCS). It traces the evolution of the NFCS from its inception to the validation of its governance, action plan, and strategic communication mechanisms. The framework brings together interministerial bodies, ANACIM, research institutions, media, and local stakeholders to improve the production, translation, and dissemination of climate information. Key achievements include the operational web platform, multidisciplinary working groups, agdata hubs, advanced weather and climate research tools, and diverse dissemination channels targeting agriculture, livestock, fisheries, and disaster risk management. Despite progress, challenges remain in governance functionality, sustainable financing, digitalization, capacity building, and alignment with national development frameworks.